The undomestic goddess - Kinsella, Sophie (1New York bestselling author, 2005)
Workaholic attorney Samantha Sweeting has just done the unthinkable. She's made a mistake so huge, it'll wreck any chance of a partnership. Going into utter meltdown, she walks out of her London office, gets on a train, and ends up in the middle of nowhere. Asking for directions at a big, beautiful house, she's mistaken for an interviewee and finds herself being offered a job as housekeeper. Her employers have no idea they've hired a lawyer--and Samantha has no idea how to work the oven. She can't sew on a button, bake a potato, or get the ironing board to open. How she takes a deep breath and begins to cope--and finds love--is a story as delicious as the bread she learns to bake